Microbiological Quality Assessment of Popular Fresh Date Samples Available in Local Outlets of Dhaka City, Bangladesh - Rausan Zamir; A. B. M. Nazmul Islam; Anisur Rahman; Sunzid Ahmed; M. Omar Faruque (International Journal of Food Science)
It is evident that date fruits provide a wide variety of essential nutrients which impart potential human health benefits. In Bangladesh, the popularity of date and its consumption surge few-fold during Ramadan among Muslims owing to the profound emotion related to religious belief that breaking of dawn-to-dusk fasting with dates is fulfilling a Sunnah. The present study aimed to explore the microbiological quality of the five most popular fresh date samples (Nagal, Dhapas, Boroi, Morium, and Tunisia) purchased from different locations of Dhaka City, Bangladesh. Among 25 samples tested, 23 were observed to carry 3.30-5.65 Log CFU/gm aerobic bacteria and 3.30-5.36 Log CFU/gm yeasts and molds population. Coliform bacteria and Escherichia coli were not found in any of the samples analyzed in this study. However, except Nagal and Boroi from Mohammadpur and Mirpur, respectively, none of the samples were found safe to consume according to the microbiological grade recommended by Woolworths Quality Assurance Standard (WQAS), 2009, as fresh dates with microbial load can cause food poisoning or even foodborne intoxication. Date samples with less or no processing is responsible for this contamination which can be subsided and eliminated by appropriate handling and hygiene practices during postharvest processing.